Therapeutic Dilemmas in Acute Ischemic Strokes and Concomitant Cardiac Thromboembolism: Case Series - Rajish Sanjit Kumar Shil; Mohamed Salah Gamea; Noor Ullah Hussaini Mohammed; Renganathan Radhakrishnan (Current Innovations in Medicine and Medical Science Vol. 3, 2022)
Ischemic stroke is a leading cause of morbidity and mortality worldwide. Anticoagulation therapy in patients with cerebral ischemic events caused by cardiac emboli is no longer debatable. The issue is deciding when to begin. Because of a recurrence rate of 15 to 20% in the first few weeks after the initial event, direct anticoagulation with intravenous heparin followed by oral anticoagulants appears to be indicated. The objective of this study is about managing patients with acute ischemic strokes and risks of development of embolic events taking into account the risks of hemorrhagic complications while treating them. We present two cases of patients who had a cardio-embolic stroke due to cardiac thrombosis and were in a therapeutic quandary about when to begin anticoagulation treatment. Early anticoagulation treatment was associated with favourable clinical and neurological outcomes.